Pentingnya Pendidikan Karakter Sejak Dini Dalam Dunia Pendidikan - Bayu Retno; Desrianti Sahida; Dodo Tomi; Sutrisno Sutrisno; MS Viktor Purhanudin; Joni Wilson Sitopu (Journal on Education, 2023)
Character education is a system of naming character values that includes components of knowledge, awareness or will, and actions to implement these values, both towards God Almighty, oneself, others, the environment, and nationality. Character of education, it is absolutely necessary not only in school but also at home, in the social environment. Event now this is no longer a participant character of education early childhood through adolescence but also adults. Absolutely necessary for the survival of this nation. Competition imagine what will emerge in the next years. Obviusly it would be our burden and parent for today. At that time, the children will face competition with colleagues from various countries around the world. In fact we are still going to work year will feel the same feelings. Demand the quality of human resources in the coming millennium certainly requires good character. However, the character is the key individual goal